Assessment of Damage by the Rice Moth, Corcyra cephalonica (81.) on Different Grains at Four Levels of Moisture Content. - Osman, Noorma (1984)
Assessment of damage by C.cephalonica on millet, sorghum, milled rice and padi at four moisture contents was determined using the count and weigh method. The parameters determined were percent damaged kernels, percent dry weight loss and dry weight of frass and webbings. The percent survival and the average development period of 12 ± 12 ~hr- old larva to adult were also determined. The four moisture contents used in this study did not influence the percent of damaged kernels, percent dry weight loss or the dry weight of frass and webbings. Rough rice was the least damaged of all the four grains; few larvae survived. The percent of larvae that survived to adult showed an increase from 11.1% MG to 13.2% MG for millet, sorghum and milled rice while at 14.1% MG, it decreased. For milled rice, the percent of larvae that survived at the lowest MG was significantly lower than at the highest MG. The development period in millet, sorghum and milled rice was significantly lower at the lowest MG.